2022
DOI: 10.1186/s13023-022-02373-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the genotypic profile and its relationship with the clinical manifestations in people with cystic fibrosis: study from a rare disease registry

Abstract: Background Cystic fibrosis (CF) has a vast and heterogeneous mutational spectrum in Europe. This variability has also been described in Spain, and there are numerous studies linking CFTR variants with the symptoms of the disease. Most of the studies analysed determinate clinical manifestations or specific sequence variants in patients from clinical units. Others used registry data without addressing the genotype–phenotype relationship. Therefore, the objective of this study is to describe the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
2
5
0
Order By: Relevance
“…However, in the genotype-adjusted model, only this and the development of CF-related liver disease and bone abnormalities were independent predictors of mortality and transplantation. These data are consistent with a previous study in which an association was found between the high-risk genotype and the most severe symptoms 24 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, in the genotype-adjusted model, only this and the development of CF-related liver disease and bone abnormalities were independent predictors of mortality and transplantation. These data are consistent with a previous study in which an association was found between the high-risk genotype and the most severe symptoms 24 .…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the genotype has been reported as one of the most determining factors both in the phenotype and in the survival of people with CF 32 . The Region of Murcia is one of the regions that has described a lower allelic frequency of the p. Phe508del variant both at the national and European level and with a high percentage of heterozygous forms 24,33 . This fact may explain to a large extent because 33% of patients for whom genetic information was available have low-risk genotypes that have been associated with higher survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When considering certain genetic mutations related to more severe disease, there were no differences between the two study groups. 36,37 In our genetic study, the predominant mutation in the patients who presented with atelectasis was the heterozygous F508del (p.Phe508del) mutation (54.5%), followed by the homozygous F508del mutation (21.8%), which were almost identical to the findings in the latest European registry. 32 No relationship has been observed between genotype and pulmonary complications, possibly because the genotype–phenotype correlation is weaker for lung disease than for other comorbidities, although there are no specific studies for lung atelectasis, excluding our study.…”
Section: Discussionsupporting
confidence: 85%